Dynamic testing and numerical simulation of human-induced vibration of cantilevered floor with tuned mass dampers. (December 2021) - Liu, Kaifang; Liu, Lulu; Zhu, Qiankun; Liu, Yanhui; Zhou, Fulin
Abstract: The vibration control of a cantilevered floor with tuned mass dampers (TMDs) was investigated using dynamic testing and numerical simulation methods to better satisfy the structural serviceability requirement. The human-induced vibration response under walking and running conditions were firstly presented based on a series of dynamic testing with a single pedestrian and groups of pedestrians. A fast-evaluated frequency response function (FRF) method suggested by AISC Design Guide 11 was also used to evaluate the vibration response and further verified by the dynamic testing. A passive TMDs system was applied to reduce the vibration response; the vibration control of the cantilevered floor with TMDs was also evaluated by the dynamic testing with a single pedestrian and groups of pedestrians. The results showed that the maximum acceleration response of the cantilevered floor under the running load exceeded the limit, which was on average nine times that of the values under the walking condition. The FRF method could provide a fast and conservative vibration evaluation, in which the maximum acceleration response was 26% higher than that from dynamic testing. The acceleration response was significantly reduced with a maximum reduction effect of 64% after the installation of TMDs, resulting in satisfactory vibration serviceability of the cantilevered floor; the numerical simulation of that agreed well with the dynamic testing results. The vibration control of the cantilevered floor as a case study can serve as reference for the application of TMDs.